Statistical Analysis of Current Guava Production and Its Prospect in Bangladesh - Hossen, Sayed Mohibul (Asian Business Review, 2012)
Agriculture is an important sector for the overall development of any country like Bangladesh. Guava is a major crop of Bangladesh, which has a significant demand in the local market. In this research, we have made a market study of guava by using time series agricultural data. The aim of the research is to know the cultural practices of guava and to study market model of guava in Bangladesh and to identify the best model that may be used for forecasting purposes. Three models (CLRM, ANCOVA and Log-Lin regression model) have been considered in this study. Ordinary least square (OLS) procedures have been used for estimation purpose. Reliable parameter estimates of the CLRM, ANCOVA and Log-Lin regression (Shil & Nath, 2008) model with minimum standard errors, high explanatory power have been obtained in this research.